DTM polyurethane coating and preparation method thereof
By using modified hydroxyl acrylic resin and modified MXENE in DTM polyurethane coatings, the existing DTM coatings have poor aging and corrosion corrosion of the existing DTM coatings under high salt, high humidity conditions, and realize the high adhesion and weather resistance of coating And corrosion resistance.
Patent Information
- Application Number
- CN202411655560.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
The existing DTM coatings age under high salt and high humidity conditions, have poor corrosion resistance, and the coating is prone to premature failure, resulting in problems such as pitting and rust permeability of metal substrates.
By adding modified hydroxyl acrylic resin and modified MXENE to DTM polyurethane coatings, increase the active group, improve the cross -linking density of HDI trioma, isolate diocyanate Effectiveness, weather resistance and corrosion resistance.
Significantly improves the adhesion, weather resistance and corrosion resistance of DTM polyurethane coatings, extends the service life of the coating, and enhances the protection of metal substrates.
Smart Images

Figure BDA0005142028260000133 
Figure BDA0005142028260000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a DTM polyurethane coating and a preparation method thereof. Background Art
[0002] The corrosion of metal materials exists in all walks of life, which will not only cause serious economic losses, but also may bring environmental problems and a series of safety problems. In order to solve the above problems, the use of organic coatings directly applied to the metal surface is the most direct, simple, and economical method. DTM paint is very popular in the industrial coating industry. It has the advantages of simple and fast construction and strong environmental protection. However, there are still many problems with the current DTM coatings. For example, the corrosion resistance of existing DTM coatings is relatively poor, and the coating is prone to premature loss of protection; the protected metal substrate is prone to pitting, rust and other defects, thereby destroying the durability of the coating, causing the coating to fail prematurely; the comprehensiveness of existing DTM coatings is generally poor, and it is easy to age under high salt and high humidity conditions. Therefore, it is of great significance to provide a DTM polyurethane coating and a preparation method thereof to solve the problems of poor salt water resistance, salt spray resistance, adhesion, weather resistance, etc. of existing DTM paints. Summary of the invention
[0003] In view of the poor salt water resistance, corrosion resistance, salt spray resistance, adhesion, weather resistance and the like of the existing DTM paint, the present invention provides a DTM polyurethane coating, which provides a large number of active groups by selecting modified hydroxyl acrylic resin and modified MXene, increases the crosslinking density with HDI trimer and isophorone diisocyanate, and forms a solid film-like protective layer, thereby improving the adhesion, weather resistance and corrosion resistance of the DTM polyurethane coating.
[0004] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0005] A DTM polyurethane coating comprises a component A and a component B;
[0006] The component A comprises the following raw materials in percentage by mass: 30%-40% of modified hydroxy acrylic resin, 8%-10% of modified MXene, 0.4%-0.6% of dispersant, 0.2%-0.5% of first defoamer, 1.5%-3% of anti-settling agent, 20%-30% of pigment, 15%-20% of filler, 0.2%-0.5% of leveling agent, 0.5%-1% of light stabilizer, 1%-2% of ultraviolet absorber and 5%-10% of first solvent;
[0007] The B component comprises the following raw materials in percentage by mass: 75%-85% of HDI trimer and 15%-25% of isophorone diisocyanate;
[0008] The modified hydroxy acrylic resin is a hydroxy acrylic resin modified by polyaspartic acid ester and a silane coupling agent;
[0009] The modified MXene is a MXene modified with a hydroxy acrylic resin.
[0010] Compared with the prior art, the DTM polyurethane coating provided by the present invention adds modified hydroxyl acrylic resin and modified MXene; wherein, the modified hydroxyl acrylic resin contains chemical bonds such as hydroxyl, secondary amino, carboxyl, epoxy or siloxane, which can not only form a solid film-like protective layer and improve the anti-corrosion performance of the coating, but also greatly improve the adhesion of the coating by improving the bonding ability between the organic coating and the substrate; the modified hydroxyl acrylic resin has a higher hydroxyl content, which increases the crosslinking density of components A and B, making the reaction more sufficient, thereby increasing the molecular weight of the coating network structure, and further improving the corrosion resistance and weather resistance of the coating; the modified hydroxyl acrylic resin contains more secondary amino groups, which react with the HDI trimer in component B to form a high-density urea bond, thereby improving the weather resistance and corrosion resistance of the coating by increasing the crosslinking density of the coating; the addition of silane coupling agent can also tightly connect the resin and the substrate together, thereby further improving the adhesion of the coating. MXene modified by hydroxyl acrylic resin has excellent chemical stability and thermal stability, and can form a dense protective film on the metal surface, thereby improving the corrosion resistance of the coating. The present invention provides a large number of active groups by adding modified hydroxy acrylic resin and modified MXene, thereby increasing the crosslinking density between the modified hydroxy acrylic resin and HDI trimer and isophorone diisocyanate, and improving the adhesion, weather resistance and corrosion resistance of the DTM polyurethane coating by forming a solid film-like protective layer.
[0011] Preferably, the modified hydroxy acrylic resin comprises the following raw materials in percentage by mass: 80%-84% hydroxy acrylic resin, 10%-12% polyaspartic acid ester, 3%-5% propylene glycol methyl ether acetate and 2.5%-3.5% silane coupling agent.
[0012] The hydroxy acrylic resin is modified by selecting polyaspartic acid ester and silane coupling agent, wherein the three raw materials undergo a cross-linking reaction so that the prepared modified hydroxy acrylic resin contains abundant groups such as hydroxyl, secondary amino, carboxyl, epoxy or siloxane. These chemical groups improve the adhesion with the metal substrate and form a dense protective film, thereby improving the adhesion, corrosion resistance and weather resistance of the coating.
[0013] Preferably, the molecular weight of the hydroxy acrylic resin is 4000-5000, the glass transition temperature is 29° C.-31° C., the solid content is 78%-82%, and the hydroxyl content is 2.3%-2.5%.
[0014] Preferably, the polyaspartic acid ester is at least one of Shenzhen Feiyang F220, Shenzhen Feiyang F221, Bayer NH1420 or Shenzhen Feiyang F321.
[0015] Preferably, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0016] The inventors have shown through a large number of studies that the use of γ-glycidyloxypropyltrimethoxysilane as a silane coupling agent has the best effect on improving the adhesion, corrosion resistance and weather resistance of the coating.
[0017] Further preferably, the silane coupling agent is at least one of Nanjing Nengde KH560, Yangzhou Lida LD-3168 or Maitu coatosil mp200.
[0018] Preferably, the preparation method of the modified hydroxy acrylic resin comprises the following steps:
[0019] The weighed hydroxy acrylic resin, propylene glycol methyl ether acetate and polyaspartic acid ester are mixed uniformly, and after adding a silane coupling agent, the mixture is kept warm at 60° C.-70° C. for reaction to obtain the modified hydroxy acrylic resin.
[0020] Preferably, the conditions for uniform mixing are: a stirring rate of 200 r / min-300 r / min, and a stirring time of 3 min-5 min.
[0021] Preferably, the insulation reaction time is 2.5h-3h.
[0022] Preferably, the modified MXene comprises the following raw materials in percentage by weight: Ti 3 C 2 T x MXene 5%-10%, hydroxy acrylic resin 80%-85%, the second defoaming agent 0.3%-0.6% and the second solvent 6%-10%.
[0023] The present invention combines the cross-linked structure of hydroxy acrylic resin with the layered structure of MXene to make the prepared modified MXene have a special structure, which can significantly improve the weather resistance and anti-corrosion performance of the coating; the hydroxyl group in the hydroxy acrylic resin can also react with Ti 3 C 2 T x The functional groups on the MXene surface undergo chemical reactions to form chemical bonds, thereby enhancing the adhesion between the coating and the metal substrate.
[0024] Preferably, the Ti 3 C 2 T xThe preparation method of MXene refers to invention patent CN114958056A.
[0025] Preferably, the hydroxylated acrylic resin is Covestro Uracron 7120S60 or Allnex D At least one of A160SN.
[0026] Preferably, the second defoaming agent is any one of German BYK 066N, BASF EFKA 2722 or Evonik TEGO 931.
[0027] Preferably, the second solvent is at least one of propylene glycol methyl acetate or butyl acetate.
[0028] Preferably, the preparation method of the modified MXene comprises the following steps:
[0029] Step 1, adding the weighed second defoamer to the hydroxy acrylic resin, mixing evenly, to obtain a primary mixed hydroxy acrylic resin;
[0030] Step 2, adding a second solvent to the primary mixed hydroxyl acrylic resin until the viscosity is 60s-80s, to obtain a mixed hydroxyl acrylic resin;
[0031] Step 3: 3 C 2 T x MXene is added to the mixed hydroxyl acrylic resin, mixed evenly, and ground to obtain modified MXene with a fineness of 20 μm-25 μm.
[0032] Further preferably, in step 1, the conditions for uniform mixing are: a stirring rate of 500 r / min-600 r / min, and a stirring time of 3 min-5 min.
[0033] Further preferably, in step 2, the second solvent can be added in batches.
[0034] Further preferably, in step 3, the conditions for uniform mixing are: stirring at a rate of 500 r / min-600 r / min for 3 min-5 min, and then dispersing at a rate of 1000 r / min-1500 r / min for 15 min-20 min.
[0035] Preferably, the dispersant is any one of a polyphosphate solution containing a pigment affinity group, a modified polyurethane polymer containing a pigment affinity group, or a modified polyurethane containing a pigment affinity group.
[0036] Further preferably, the dispersant is any one of BYK110, AFCONA-4071 or EFKA-4010.
[0037] Preferably, the first defoaming agent is any one of a fluorosilicone-modified polysiloxane defoaming agent, an organosilicon defoaming agent, a silicon-containing defoaming agent or a fluorosilicone solution.
[0038] Further preferably, the first defoaming agent is any one of BYK-066N, EFKA 2722 or Tego 931.
[0039] Preferably, the anti-settling agent is a mixture of a powdery anti-settling agent and a paste-like anti-settling agent.
[0040] Further preferably, the mass ratio of the powdery anti-settling agent to the paste anti-settling agent in the anti-settling agent is (1-2):(1-2).
[0041] Further preferably, the powdered anti-settling agent is fumed silica or organic bentonite.
[0042] Further preferably, the paste anti-settling agent is polyamide wax or polyethylene wax.
[0043] Further preferably, the anti-settling agent is at least one of American Cabot M5, Deqian SD-2, Sparron 6900-20, Disparron 4200-20 or Deqian 202P.
[0044] Preferably, the pigment is at least two of titanium dioxide, zinc phosphate or C500.
[0045] Further preferably, the mass ratio of titanium dioxide, zinc phosphate and C500 in the pigment is (3.7-4):1:(0-1).
[0046] Preferably, the filler is a mixture of talc and barium sulfate.
[0047] Further preferably, the mass ratio of talc powder to barium sulfate in the filler is 1:(1.5-2).
[0048] Further preferably, the fineness of the talcum powder is 1200-1300 mesh.
[0049] Further preferably, the fineness of the barium sulfate is 1200-1300 mesh.
[0050] Preferably, the leveling agent is at least one of an acrylic leveling agent or a polyether-modified dimethylsiloxane.
[0051] Further preferably, the leveling agent is at least one of EFKA3777, LHP-95 or BYK-306.
[0052] Preferably, the light stabilizer is a hindered amine light stabilizer.
[0053] Further preferably, the light stabilizer is at least one of TINUVIN-292 or Eversorb93.
[0054] Preferably, the ultraviolet absorber is a benzotriazole ultraviolet absorber.
[0055] Further preferably, the ultraviolet absorber is at least one of TINUVIN-1130 or Eversorb80.
[0056] Preferably, the first solvent is a mixture of propylene glycol methyl acetate and butyl acetate.
[0057] Further preferably, the mass ratio of propylene glycol methyl acetate to butyl acetate in the first solvent is 1:(1-2).
[0058] Preferably, the model of the HDI trimer is Bayer N3390 or Wanhua HT-90B.
[0059] Preferably, the isophorone diisocyanate is Bayer Z4470 or Wanhua IT-170B.
[0060] Preferably, the mass ratio of component A to component B is (7-9):1.
[0061] The present invention also provides a method for preparing the above-mentioned DTM polyurethane coating, comprising the following steps:
[0062] Step a, weighing each raw material according to the mass ratio, and uniformly mixing the weighed modified hydroxy acrylic resin, dispersant, leveling agent, light stabilizer, ultraviolet absorber, first defoaming agent and anti-settling agent to obtain a first mixed slurry;
[0063] Step b, adding the pigment and filler to the first mixed slurry, then adding the first solvent until the viscosity is 100s-120s, mixing evenly, grinding, and obtaining a second mixed slurry with a fineness of 20μm-25μm;
[0064] Step c, adding the modified MXene to the second mixed slurry, mixing evenly, to obtain the component A;
[0065] Step d, mixing the weighed HDI trimer and isophorone diisocyanate uniformly to obtain the B component;
[0066] Step e: uniformly mixing the component A and the component B to obtain the DTM polyurethane coating.
[0067] Further preferably, in step a, the weighed modified hydroxy acrylic resin, dispersant, leveling agent, light stabilizer, UV absorber, first defoaming agent and paste anti-settling agent are stirred for 3min-5min at a rate of 600r / min-700r / min, and then the powdered anti-settling agent is added and stirred at a rate of 300r / min-500r / min for 3min-5min to obtain a first mixed slurry.
[0068] Further preferably, in step b, the conditions for uniform mixing are: a stirring rate of 800 r / min-1000 r / min, and a stirring time of 15 min-20 min.
[0069] Further preferably, in step c, the conditions for uniform mixing are: a stirring rate of 1000 r / min-1200 r / min, and a stirring time of 15 min-18 min.
[0070] Further preferably, in step d, the conditions for uniform mixing are: a stirring rate of 600 r / min-800 r / min, and a stirring time of 15 min-20 min.
[0071] The preparation method provided by the invention is simple to operate, has no complicated steps, does not require special equipment, has low cost, is suitable for industrial large-scale production, and has broad market prospects and development potential. DETAILED DESCRIPTION
[0072] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0073] Example 1
[0074] The present embodiment provides a DTM polyurethane coating, comprising a component A and a component B in a mass ratio of 7:1; the component A comprises the following raw materials in mass percentage: 40% of modified hydroxy acrylic resin, 10% of modified MXene, 0.4% of BYK110, 0.5% of BYK-066N, 1.5% of anti-settling agent, 20% of titanium dioxide, 5.4% of zinc phosphate, 5% of talc powder with a fineness of 1200 mesh, 10% of barium sulfate with a fineness of 1200, 0.2% of EFKA3777, 1% of TINUVIN-292, 1% of TINUVIN-1130, and 5% of a first solvent; wherein the anti-settling agent is a mixture of fumed silica and polyamide wax in a mass ratio of 1:2; the first solvent is a mixture of propylene glycol methyl acetate and butyl acetate in a mass ratio of 1:1;
[0075] The B component includes the following raw materials in percentage by mass: Bayer N3390 75%, Bayer Z4470 25%;
[0077] The modified hydroxy acrylic resin comprises the following raw materials in percentage by mass: 80% hydroxy acrylic resin, 12% Shenzhen Feiyang F220, 5% propylene glycol methyl ether acetate, and 3% Nanjing Nengde KH560; wherein the hydroxy acrylic resin has a molecular weight of 5000, a glass transition temperature of 30°C, a solid content of 80%, and a hydroxyl content of 2.4%;
[0078] The preparation method of the modified hydroxy acrylic resin comprises the following steps:
[0079] The weighed hydroxy acrylic resin, propylene glycol methyl ether acetate and Shenzhen Feiyang F220 were stirred at a rate of 200 r / min for 3 minutes, and Nanjing Nengde KH560 was added and kept at 70° C. for 2.5 hours to obtain the modified hydroxy acrylic resin;
[0080] The modified MXene includes the following raw materials in percentage by weight: Ti 3 C 2 T x MXene 10%, Covestro Uracron 7120S60 80%, German BYK 066N 0.6%, propylene glycol methyl acetate 9.4%;
[0081] The preparation method of the modified MXene comprises the following steps:
[0082] Step 1, adding the weighed BYK 066N from Germany into Covestro Uracron 7120S60, stirring at a rate of 600 r / min for 5 minutes to obtain a primary mixed hydroxyl acrylic resin;
[0083] Step 2, adding propylene glycol methyl acetate to the primary mixed hydroxyl acrylic resin until the viscosity is 80s to obtain a mixed hydroxyl acrylic resin;
[0084] Step 3: 3 C 2 T x MXene was added to the mixed hydroxylated acrylic resin, stirred at a rate of 600 r / min for 5 min, then dispersed at a rate of 1000 r / min for 20 min, and ground to obtain a modified MXene with a fineness of 25 μm;
[0085] The preparation method of the DTM polyurethane coating comprises the following steps:
[0086] Step a, at a rate of 700 r / min, the weighed modified hydroxyl acrylic resin, BYK110, EFKA3777, TINUVIN-292, TINUVIN-1130, BYK-066N and polyamide wax were stirred for 5 min, and then fumed silica was added, and stirred at a rate of 300 r / min for 5 min to obtain a first mixed slurry;
[0087] Step b, adding the titanium dioxide, zinc phosphate, talcum powder and barium sulfate to the first mixed slurry, then adding the first solvent until the viscosity is 100s, stirring at a rate of 1000r / min for 20min, grinding to obtain a second mixed slurry with a fineness of 25μm;
[0088] Step c, adding the modified MXene to the second mixed slurry, stirring at a rate of 1000 r / min for 15 min, to obtain the component A;
[0089] Step d, stirring the weighed HDI trimer and isophorone diisocyanate at a rate of 600 r / min for 20 min to obtain the B component;
[0090] Step e: uniformly mixing the component A and the component B to obtain the DTM polyurethane coating.
[0091] Example 2
[0092] The present embodiment provides a DTM polyurethane coating, comprising a component A and a component B in a mass ratio of 9:1; the component A comprises the following raw materials in mass percentage: 30% modified hydroxy acrylic resin, 8% modified MXene, 10.6% AFCONA-407, 0.5% EFKA 2722, 3% anti-settling agent, 20% titanium dioxide, 5% zinc phosphate, 5% C500, 10% barium sulfate with a fineness of 1200 mesh, 5.1% talc with a fineness of 1300 mesh, 0.3% LHP-95, 0.5% Eversorb93, 2% Eversorb80, and 10% first solvent; wherein the anti-settling agent is a mixture of organic bentonite and polyethylene wax in a mass ratio of 2:1; the first solvent is a mixture of propylene glycol methyl acetate and butyl acetate in a mass ratio of 1:2;
[0093] The B component includes the following raw materials in percentage by mass: 85% HDI trimer and 15% isophorone diisocyanate;
[0094] The modified hydroxy acrylic resin comprises the following raw materials in percentage by mass: 84% hydroxy acrylic resin, 10% Shenzhen Feiyang F221, 3% propylene glycol methyl ether acetate, and 3% Yangzhou Lida LD-3168; wherein the hydroxy acrylic resin has a molecular weight of 4000, a glass transition temperature of 29°C, a solid content of 82%, and a hydroxyl content of 2.5%;
[0095] The preparation method of the modified hydroxy acrylic resin comprises the following steps:
[0096] The weighed hydroxy acrylic resin, propylene glycol methyl ether acetate and Shenzhen Feiyang F221 were stirred at a rate of 300 r / min for 5 min, and Yangzhou Lida LD-3168 was added and kept at 60° C. for 3 h to obtain the modified hydroxy acrylic resin;
[0097] The modified MXene includes the following raw materials in percentage by weight: Ti 3 C 2 T x MXene 5%, allnex DA 160SN 85%, BASF EFKA 2722 0.6%, butyl acetate 9.4%;
[0098] The preparation method of the modified MXene comprises the following steps:
[0099] Step 1: Add the weighed EFKA 2722 to the D A160SN, stirring at a rate of 500 r / min for 3 min to obtain a primary mixed hydroxyl acrylic resin;
[0100] Step 2, adding butyl acetate to the primary mixed hydroxyl acrylic resin until the viscosity is 60s to obtain a mixed hydroxyl acrylic resin;
[0101] Step 3: 3 C 2 T x MXene was added to the mixed hydroxylated acrylic resin, stirred at a rate of 500 r / min for 3 min, then dispersed at a rate of 1500 r / min for 15 min, and ground to obtain a modified MXene with a fineness of 20 μm;
[0102] The preparation method of the DTM polyurethane coating comprises the following steps:
[0103] Step a, at a rate of 600 r / min, the weighed modified hydroxyl acrylic resin, AFCONA-4071, LHP-95, Eversorb93, Eversorb80, EFKA 2722 and polyethylene wax were stirred for 3 min, and then organic bentonite was added, and stirred at a rate of 500 r / min for 3 min to obtain a first mixed slurry;
[0104] Step b, adding the titanium dioxide, zinc phosphate, C500, talcum powder and barium sulfate to the first mixed slurry, then adding the first solvent until the viscosity is 120s, stirring at a rate of 800r / min for 15min, grinding, and obtaining a second mixed slurry with a fineness of 20μm;
[0105] Step c, adding the modified MXene to the second mixed slurry, stirring at a rate of 1200 r / min for 18 min, to obtain the component A;
[0106] Step d, stirring the weighed HDI trimer and isophorone diisocyanate at a rate of 800 r / min for 15 min to obtain the B component;
[0107] Step e: uniformly mixing the component A and the component B to obtain the DTM polyurethane coating.
[0108] Example 3
[0109] The present embodiment provides a DTM polyurethane coating, comprising a component A and a component B in a mass ratio of 8:1; the component A comprises the following raw materials in mass percentage: 32% modified hydroxy acrylic resin, 9% modified MXene, 0.6% EFKA-4010, 0.5% Tego 931, 3% anti-settling agent, 20% titanium dioxide, 5% zinc phosphate, 5% C500, 6% talc powder with a fineness of 1200 mesh, 9% barium sulfate, 0.4% BYK-306, 0.6% Eversorb93, 1.5% Eversorb80, and 7.4% first solvent; wherein the anti-settling agent is a mixture of organic bentonite and polyamide wax in a mass ratio of 2:1; the first solvent is a mixture of propylene glycol methyl acetate and butyl acetate in a mass ratio of 1:1.5;
[0110] The B component includes the following raw materials in percentage by mass: 80% HDI trimer and 20% isophorone diisocyanate;
[0111] The modified hydroxy acrylic resin comprises the following raw materials in percentage by mass: 82% hydroxy acrylic resin, 11% Bayer NH1420, 4% propylene glycol methyl ether acetate, and 3% Momentive coatosil mp200; wherein the hydroxy acrylic resin has a molecular weight of 4500, a glass transition temperature of 31° C., a solid content of 78%, and a hydroxyl content of 2.3%;
[0112] The preparation method of the modified hydroxy acrylic resin comprises the following steps:
[0113] The weighed hydroxy acrylic resin, propylene glycol methyl ether acetate and Bayer NH1420 were stirred at a rate of 250 r / min for 4 minutes, and Momentive coatosil mp200 was added and kept at 65° C. for 2.7 hours to obtain the modified hydroxy acrylic resin;
[0114] The modified MXene includes the following raw materials in percentage by weight: Ti 3 C 2 T x MXene 8%, Allnex DA 160SN 84%, Evonik TEGO931 0.5%, butyl acetate 7.5%;
[0115] The preparation method of the modified MXene comprises the following steps:
[0116] Step 1: Add the weighed Evonik TEGO931 into Allnex DA 160SN was stirred at a rate of 550 r / min for 4 min to obtain a primary mixed hydroxyl acrylic resin;
[0117] Step 2, adding butyl acetate to the primary mixed hydroxyl acrylic resin until the viscosity is 70s to obtain a mixed hydroxyl acrylic resin;
[0118] Step 3: 3 C 2 T x MXene was added to the mixed hydroxylated acrylic resin, stirred at a rate of 560 r / min for 4 min, then dispersed at a rate of 1200 r / min for 18 min, and ground to obtain a modified MXene with a fineness of 22.5 μm;
[0119] The preparation method of the DTM polyurethane coating comprises the following steps:
[0120] Step a, at a rate of 680 r / min, the weighed modified hydroxyl acrylic resin, EFKA-4010, BYK-306, Eversorb93, Eversorb80, Tego 931 and polyethylene wax were stirred for 4 min, and then organic bentonite was added, and stirred at a rate of 400 r / min for 4 min to obtain a first mixed slurry;
[0121] Step b, adding the titanium dioxide, zinc phosphate, C500, talcum powder and barium sulfate to the first mixed slurry, then adding the first solvent until the viscosity is 110s, stirring at a rate of 900r / min for 18min, grinding, and obtaining a second mixed slurry with a fineness of 22.5μm;
[0122] Step c, adding the modified MXene to the second mixed slurry, stirring at a rate of 1100 r / min for 16 min, to obtain the component A;
[0123] Step d, stirring the weighed HDI trimer and isophorone diisocyanate at a rate of 700 r / min for 18 min to obtain the B component;
[0124] Step e: uniformly mixing the component A and the component B to obtain the DTM polyurethane coating.
[0125] Example 4
[0126] This embodiment provides a DTM polyurethane coating, which is different from Embodiment 3 in that:
[0127] The Momentive coatosil mp200 in Example 3 was replaced with an equal amount of γ-aminopropyltriethoxysilane KH-550;
[0128] The other components and operating steps are the same as those in Example 3.
[0129] Comparative Example 1
[0130] This comparative example provides a DTM polyurethane coating, which is different from Example 3 in that:
[0131] The Bayer NH1420 in Example 3 was replaced by an equal amount of polyester resin 670BA;
[0132] The other components and operating steps are the same as those in Example 3.
[0133] Comparative Example 2
[0134] This comparative example provides a DTM polyurethane coating, which is different from Example 3 in that:
[0135] The Bayer NH1420 in Example 3 was replaced with an equal amount of high solid hydroxylated acrylic resin. FC2100SS-80;
[0136] The other components and operating steps are the same as those in Example 3.
[0137] Comparative Example 3
[0138] This comparative example provides a DTM polyurethane coating, which is different from Example 3 in that:
[0139] The Covestro Uracron 7120S60 in the modified MXene raw material of Example 3 was replaced with an equal amount of polyester resin 680BA;
[0140] The other components and operating steps are the same as those in Example 3.
[0141] Comparative Example 4
[0142] This comparative example provides a DTM polyurethane coating, which is different from Example 3 in that:
[0143] The Ti in Example 3 3 C 2 T x MXene was replaced with an equal amount of graphene;
[0144] The other components and operating steps are the same as those in Example 3.
[0145] The coatings provided in Examples 1-4 and Comparative Examples 1-4 were tested, wherein the applicable period was tested with reference to the test standard HG / T5368-2018 "Polyaspartic acid anticorrosive coatings", and the surface drying time, actual drying time, film appearance, gloss, impact resistance, adhesion (cross-hatch method), salt water resistance, salt spray resistance, and resistance to artificial accelerated aging were tested with reference to the test standard HG / T2454-2014 "Solvent-based polyurethane coatings (two-component)". The specific test results are shown in Table 1:
[0146] Table 1
[0147]
[0148]
[0149] The DTM polyurethane coating prepared in the embodiment of the present invention provides a large number of active groups by adding modified hydroxyl acrylic resin and modified MXene, thereby increasing the crosslinking density between the DTM polyurethane coating and HDI trimer and isophorone diisocyanate, and improving the adhesion, weather resistance and corrosion resistance of the DTM polyurethane coating by forming a strong film-like protective layer.
[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A DTM polyurethane coating, characterized in that: The DTM polyurethane coating comprises component A and component B; The A component includes the following raw materials in percentage by mass: 30%-40% of modified hydroxy acrylic resin, 8%-10% of modified MXene, 0.4%-0.6% of dispersant, 0.2%-0.5% of first defoamer, 1.5%-3% of anti-settling agent, 20%-30% of pigment, 15%-20% of filler, 0.2%-0.5% of leveling agent, 0.5%-1% of light stabilizer, 1%-2% of ultraviolet absorber and 5%-10% of first solvent; The B component comprises the following raw materials in percentage by mass: 75%-85% of HDI trimer and 15%-25% of isophorone diisocyanate; The modified hydroxy acrylic resin is a hydroxy acrylic resin modified by polyaspartic acid ester and a silane coupling agent; The modified MXene is a MXene modified with a hydroxy acrylic resin.
2. The DTM polyurethane coating according to claim 1, characterized in that: The modified hydroxy acrylic resin comprises the following raw materials in percentage by mass: 80%-84% of hydroxy acrylic resin, 10%-12% of polyaspartic acid ester, 3%-5% of propylene glycol methyl ether acetate and 2.5%-3.5% of silane coupling agent.
3. The DTM polyurethane coating according to claim 2, characterized in that: The molecular weight of the hydroxy acrylic resin is 4000-5000, the glass transition temperature is 29° C.-31° C., the solid content is 78%-82%, and the hydroxyl content is 2.3%-2.5%.
4. The DTM polyurethane coating according to claim 2, characterized in that: The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
5. The DTM polyurethane coating according to any one of claims 2 to 4, characterized in that: The preparation method of the modified hydroxy acrylic resin comprises the following steps: The weighed hydroxy acrylic resin, propylene glycol methyl ether acetate and polyaspartic acid ester are mixed uniformly, and after adding a silane coupling agent, the mixture is kept warm at 60° C.-70° C. for reaction to obtain the modified hydroxy acrylic resin.
6. The DTM polyurethane coating according to claim 1, characterized in that: The modified MXene includes the following raw materials in percentage by weight: Ti3C2T x MXene 5%-10%, hydroxy acrylic resin 80%-85%, the second defoaming agent 0.3%-0.6% and the second solvent 6%-10%.
7. The DTM polyurethane coating according to claim 6, characterized in that: The preparation method of the modified MXene comprises the following steps: Step 1, adding the weighed second defoamer to the hydroxy acrylic resin, mixing evenly, to obtain a primary mixed hydroxy acrylic resin; Step 2, adding a second solvent to the primary mixed hydroxyl acrylic resin until the viscosity is 60s-80s, to obtain a mixed hydroxyl acrylic resin; Step 3: The Ti3C2T x MXene is added to the mixed hydroxyl acrylic resin, mixed evenly, and ground to obtain modified MXene with a fineness of 20 μm-25 μm.
8. The DTM polyurethane coating according to claim 1, characterized in that: The first defoamer is any one of a fluorosilicone-modified polysiloxane defoamer, an organosilicon defoamer, a silicon-containing defoamer or a fluorosilicone solution.
9. The DTM polyurethane coating according to claim 1, characterized in that: The mass ratio of component A to component B is (7-9):
1.
10. A method for preparing the DTM polyurethane coating according to any one of claims 1 to 9, characterized in that: The steps include: Step a, weighing each raw material according to a ratio, and uniformly mixing the weighed modified hydroxy acrylic resin, dispersant, leveling agent, light stabilizer, ultraviolet absorber, first defoaming agent and anti-settling agent to obtain a first mixed slurry; Step b, adding the pigment and filler to the first mixed slurry, then adding the first solvent until the viscosity is 100s-120s, mixing evenly, grinding, and obtaining a second mixed slurry with a fineness of 20μm-25μm; Step c, adding the modified MXene to the second mixed slurry, mixing evenly, to obtain the component A; Step d, mixing the weighed HDI trimer and isophorone diisocyanate uniformly to obtain the B component; Step e: uniformly mixing the component A and the component B to obtain the DTM polyurethane coating.
Citation Information
Patent Citations
Ti3C2Tx and ZnAl-MoO4 LDH composite corrosion inhibitor and preparation method and composite coating thereof
CN114958056A